2019
DOI: 10.1021/jacs.8b13366
|View full text |Cite|
|
Sign up to set email alerts
|

Probing Size and Substrate Effects on the Hydrogen Evolution Reaction by Single Isolated Pt Atoms, Atomic Clusters, and Nanoparticles

Abstract: We report the catalytic activity of a single, isolated Pt deposit on Bi and Pb supports to probe the size and substrate effects on the electrochemical hydrogen evolution reaction (HER). Deposits were made electrolytically by an atom-by-atom method in a controlled plating; we prepared an individual Pt deposit on Bi and Pb ultramicroelectrodes (UMEs) such as a single isolated atom, clusters containing one to five Pt atoms, and nanoparticles to about 10 nm radius. A steady-state voltammogram on the single Pt depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 32 publications
2
104
1
Order By: Relevance
“…There are several examples in the literature of a NC/NP losing its catalytic activity below a certain size. For example, Bard and coworkers recently showed that the catalytic activity of Pt NPs for the HER increased with increasing Pt NP size from 0.25 nm to 0.75 nm, indicating that there is an optimum size of NPs for their specific catalytic applications . Our results indicate that the HER and CO 2 RR is favored with THPC Au 1.6nm NCs, but not favored for TPPS Au 0.9nm NCs or Cit Au 4.1nm NPs.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…There are several examples in the literature of a NC/NP losing its catalytic activity below a certain size. For example, Bard and coworkers recently showed that the catalytic activity of Pt NPs for the HER increased with increasing Pt NP size from 0.25 nm to 0.75 nm, indicating that there is an optimum size of NPs for their specific catalytic applications . Our results indicate that the HER and CO 2 RR is favored with THPC Au 1.6nm NCs, but not favored for TPPS Au 0.9nm NCs or Cit Au 4.1nm NPs.…”
Section: Resultsmentioning
confidence: 48%
“…For example, Bard and coworkers recently showed that the catalytic activity of Pt NPs for the HER increased with increasing Pt NP size from 0.25 nm to 0.75 nm, indicating that there is an optimum size of NPs for their specific catalytic applications. [60] Our results indicate that the HER and CO 2 RR is favored with THPC Au 1.6nm NCs, but not favored for TPPS Au 0.9nm NCs or Cit Au 4.1nm NPs. The lower reactivity of TPPS Au 0.9nm NCs and Cit Au 4.1nm NPs could be due to the lack of specific surface atom coordination such as edge atoms, [20] the main active site for catalytic HER with Au, [15] or due to instability or change in electronic structure in the case of the smaller TPPS Au 0.9nm NCs.…”
Section: Catalytic Propertiesmentioning
confidence: 51%
See 1 more Smart Citation
“…The inherent problems are the wide range of size distributions of metal catalysts on carbon supports, from single atoms to NPs or clusters. Zhou et al . recently reported the measurement of kinetic parameters of single Pt atoms, clusters, and NPs for HER on ultramicro electrodes.…”
Section: Prospects Of Pmg‐based Catalysts For Oxidation Of Alcoholsmentioning
confidence: 99%
“…If the Au NPs remained on the surface, then we should observe the Au peak in the ASV after ozone cleaning. We studied the TPPS Au0.9nm NPs as a catalyst for the hydrogen evolution 217 and also could be due to the instability 9 of NPs during applications.…”
Section: Resultsmentioning
confidence: 99%